A new method to estimate cloud cover fraction over El Leoncito Observatory from an all-sky imager designed for upper atmosphere studies - Martinis, C. (2013)
A method for determining cloud cover fraction over El Leoncito Observatory (31.8°S, 69.3°W) is presented. Data from an all-sky imaging system, designed to measure nightglow originating from the mesosphere and thermosphere, is used to determine the fraction of the sky covered by clouds. More than 9,000 hr of observations from May 2006 to December 2010 are used to show that El Leoncito is clear approximately 75-80% of the time. No significant seasonal variations are observed. The optical ground-based data are compared with data from the Moderate Resolution Imaging Spectro-radiometer (MODIS) instrument on board the TERRA and AQUA satellites.